Association between Hemogram Parameters and Coronary Collateral Development in Subjects with Non-ST-Elevation Myocardial Infarction - Sincer,Isa (2020)
SUMMARY OBJECTIVE Coronary collateral development (CCD) predicts the severity of coronary heart disease. Hemogram parameters, such as mean platelet volume (MPV), eosinophil, red cell distribution width, and platelet distribution width (PDW), are supposed novel inflammatory markers. We aimed to compare hemogram parameter values in patients presenting with non-ST-elevation myocardial infarction (NSTEMI) with adequate or inadequate CCD. METHODS A total of 177 patients with NSTEMI undergoing coronary arteriography were enrolled and divided into two groups based on the development of CCD: one group with adequate CCD (n=88) and the other with impaired CCD (n=89). RESULTS Baseline demographics and clinical risk factors were similar between the groups. Hemogram parameters were not significantly different between the two groups. However, compared to the inadequate CCD group, the median PDW was significantly higher in the adequate CCD group, 17.6 (1.4) vs. 17.8 (1.6) p=0.004. In a multivariate analysis, PDW (p=0.001, 95% CI for OR: 0.489(0,319-0,750) was found to be significantly different in the adequate CCD group compared to the inadequate CCD group. Pearson’s correlation analysis revealed that PDW was significantly correlated with the Rentrop score (r=0.26, p<0.001). CONCLUSIONS We suggest that since PDW is an index that is inexpensive and easy to assess, it could serve as a marker of CCD in patients with NSTEMI.